2019
DOI: 10.1159/000503689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Efficacies of Serological Markers KL-6, SP-A, SP-D, CCL2, and CXCL13 in Idiopathic Interstitial Pneumonia

Abstract: <b><i>Background:</i></b> The objective of this study was to evaluate the diagnostic value of serological markers Krebs von den Lungen-6 (KL-6), surfactant protein-A (SP-A), SP-D, chemokine ligand 2 (CCL2), and chemokine 13 (CXCL13) in idiopathic interstitial pneumonia (IIP). <b><i>Methods:</i></b> Patients with IIP aged 18–80 years from the First Affiliated Hospital of Guangzhou Medical University were enrolled in this retrospective case-control study. Data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Not much reports have focused on AID /connective tissue diseases, although patterns seen in chronic AID are very similar to IPF [40]. Even genetic alterations of surfactant and telomerase genes have been reported in AID similar to IPF [41,42]. Whereas an NSIP pattern almost exclusively is associated with AID or HP, an UIP pattern has a wider range of differentials.…”
Section: Discussionmentioning
confidence: 99%
“…Not much reports have focused on AID /connective tissue diseases, although patterns seen in chronic AID are very similar to IPF [40]. Even genetic alterations of surfactant and telomerase genes have been reported in AID similar to IPF [41,42]. Whereas an NSIP pattern almost exclusively is associated with AID or HP, an UIP pattern has a wider range of differentials.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemotactic protein 1 (MCP-1; also known as CCL2) is another monocyte activity marker and its levels are increased in people with IIP. 75 MCP-1 is significantly correlated with interstitial lung lesions. In addition, a monoclonal antibody that neutralises the fibrotic activities of MCP-1 has been used in a clinical trial.…”
Section: Monocyte Activity Markermentioning
confidence: 92%
“…Hamai et al [201] found that a combination of MMP-7 and KL-6 potentially support the diagnosis of IPF and might improve survival prediction in patients with IPF. Recently published study Xue et al [202], found that KL-6, CCL3, and CXCL13 significantly improves the diagnosis of idiopathic interstitial pneumonia. IPF patients with a high level of SP-D but low KL-6 in their serum had a better prognosis [203].…”
Section: Multimarker Approachmentioning
confidence: 98%